Resolution of family disputes: mediation vs. litigation - Abdul Hak, Nora; Abdullah, Nurdianawati Irwani; Md Hashim, Noraini; Rahmat, Nur Ezan (Faculty of Law, Universiti Kebangsaan Malaysia, 2011)
Family disputes, more often than not, are rarely concerned with matters of fact but almost invariably complicated by the intense and intimate emotions of the parties in conflict. Therefore, the utilization of Alternative Dispute Resolution (ADR) such as conciliation and mediation, independent of litigation will lead to a more satisfactory resolution of disputes rather than relying on the judgments of the court of law. It has to be borne in mind that in Malaysian society, family ties are still very strong and as such when matrimonial disputes arise and marriages are on tender-hooks, parties often seek assistance from family members to salvage the marriage. Mediation has come under the spotlight and watchful eye of many countires' legal systems for its ability to resolve conflicts between parties, reduce court case loads and reduce overall legal costs. Many jurisdictions already have existing legal provisions that give their courts the authority to order parties in dispute to mediation when deemed appropriate. In Malaysia, to encourage settlement of disputes through mediation including family disputes, the Bar Council established the Malaysian Mediation Centre (MCC) in 1999. The paper focuses on the development and advantages/merits of mediation as a suitable means of resolving family disputes as oppose to litigation. The law and the practice in some selected jurisdictions will be deliberated to study the performance of family mediation so far.